Pemanfaatan Market Place (Tokopedia) sebagai Sarana Pemasaran Produk Bagi UMKM di Kelurahan Meruya Utara - Misbahul Fajri; Yuwan Jumaryadi; Bagus Priambodo (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
With today's rapidly developing technology, SME owners need to work even harder to provide the best service to their customers. In addition, SME owners need to focus more on product marketing. Today's small business owners need to gather information to develop effective marketing methods. Indonesia has experienced a fairly high growth of Internet users. From around 2 million Internet users from a population of around 206 million people in 2000 (+/- 1% of the total population), and then grew very rapidly to around 20 million Internet users from a population of around 224 million in 2007 (+/- 10 % of the total population), then the number of Internet users increased again to around 82 million from a total population of 237 million people (about 40%) in 2013. Product marketing is an important factor in determining a company's performance. Product marketing strategy is an activity that needs to be done to introduce a product to more people. Given the above issues, it may be necessary to implement training on new marketing concepts.